2011
DOI: 10.3844/ajavsp.2011.125.129
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Feline Immunodeficiency Virus and Feline Leukemia Virus Infection in Cats

Abstract: Problem statement:The objective of the present study was to evaluate occurrence of the Feline Immunodeficiency Virus (FIV) and the Feline Leukemia Virus (FeLV) infection in asymptomatic domestic cats in the metropolitan region of Belo Horizonte, Minas Gerais, using the Polymerase Chain Reaction (PCR) for FIV detection and SNAP Combo Plus for FeLV and FIV detection. Approach: Blood samples were collected from the jugular vein of 78 healthy cats, mixed breeds and ages and both sexes. Specific primers were design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
0
5
1
1
Order By: Relevance
“…The present study showed a higher positivity percentage for the PCR technique when compared to Marçola et al (2013), that related 2% (4/200) of positive animals in Distrito Federal (GO) and to the studies done by Caxito et al (2006), Teixeira et al (2007) and Alves et al (2011), in the city of Belo Horizonte (MG) presenting values of 2.7% (12/450), 4.14% (6/145) and 6.41% (5/78), of positivity, respectively. However, the values found in São Luís (MA) were lower than the ones related by Lara et al (2008) that reported an occurrence of 14.8% (67/454) of felines from 13 cities of São Paulo state and by Souza et al (2002) who verified positivity of 20.2% in Rio de Janeiro (RJ) and even lower than those found by Caldas et al (2000) who described 37.5% (15/40) of seropositive animals in the state of Rio Grande do Sul.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…The present study showed a higher positivity percentage for the PCR technique when compared to Marçola et al (2013), that related 2% (4/200) of positive animals in Distrito Federal (GO) and to the studies done by Caxito et al (2006), Teixeira et al (2007) and Alves et al (2011), in the city of Belo Horizonte (MG) presenting values of 2.7% (12/450), 4.14% (6/145) and 6.41% (5/78), of positivity, respectively. However, the values found in São Luís (MA) were lower than the ones related by Lara et al (2008) that reported an occurrence of 14.8% (67/454) of felines from 13 cities of São Paulo state and by Souza et al (2002) who verified positivity of 20.2% in Rio de Janeiro (RJ) and even lower than those found by Caldas et al (2000) who described 37.5% (15/40) of seropositive animals in the state of Rio Grande do Sul.…”
Section: Discussionmentioning
confidence: 86%
“…The serum samples were submitted to immunochromatography, using the commercial kit SNAP Combo Plus (IDEXX ® Laboratories, USA) to verify the presence of antibodies against the FIV protein p24 and the FeLV protein p27. The indirect ELISA used was the one standardized by Alves et al (2011), using 2.5 ng/mL of the FIV recombinant protein p24 (r-p24) adsorbed onto the plate, 1:320 diluted serum and conjugated (peroxidase anti-cat IgG/SIGMA-ALDRICH) at 1:7500 dilution.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The minimum sample size was defined as 71 cats, finite population of 310 cats, with an expected prevalence of 6.4% (Alves et al 2011), an acceptable error rate of 5% and a 95% confidence interval, as defined by Epi Info 6.0 (Centers for Disease Control and Prevention [CDC], Atlanta, GA, USA). A questionnaire on the lifestyle and habits of the felines was given to each owner, followed by clinical evaluation of the felines and collection of blood samples by puncturing the jugular vein.…”
Section: Methodsmentioning
confidence: 99%
“…Transformation of normal cells to malignant cells may triggered by several factors including chemical exposure, viruses and radiations. It also can occur deliberately under cellular control during the processes such as meiosis or hypermutation (Alves et al, 2011;Lodish et al, 2000).…”
Section: Introductionmentioning
confidence: 99%